2021
DOI: 10.3390/molecules26092826
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles and Antifungal-Antibacterial-Antiviral Activity of South African Salvia spp. Essential Oils Cultivated in Uniform Conditions

Abstract: Spontaneous emissions of S. dentata Aiton and S. scabra Thunb., as well as the essential oil (EO) composition of the cited species, together with S. aurea L., were investigated. The chemical profile of the first two species is reported here for the first time. Moreover, in vitro tests were performed to evaluate the antifungal activity of these EOs on Trichophyton mentagrophytes, Microsporum canis, Aspergillus flavus, Aspergillus niger, and Fusarium solani. Secondly, the EO antibacterial activity against Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…There is evidence that nonanal is present as a metabolite in other species from the Salvia genus. For instance, 0.1% of the relative concentration percentage of nonanal was detected in Salvia scabra essential oil obtained by hydrodistillation in a Clevenger apparatus [30]. Another example of Salvia taxa with nonanal in the essential oil is Salvia argentea, which contained 0.8% [31].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that nonanal is present as a metabolite in other species from the Salvia genus. For instance, 0.1% of the relative concentration percentage of nonanal was detected in Salvia scabra essential oil obtained by hydrodistillation in a Clevenger apparatus [30]. Another example of Salvia taxa with nonanal in the essential oil is Salvia argentea, which contained 0.8% [31].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, methanol extracts of S. sclarea and S. cedronel reduced H7N7/H3N2 influenza virus strains-induced cytopathy on Madin-Darby canine kidney (MDCK) cells [ 102 , 107 ]. Similarly, recent studies reported that the methanol extract of S. plebeian and the essential oil from S. dentate inhibit the H1N1 strain of influenza virus (reducing plaque formation by 93% at 11.18 mM) [ 16 , 106 ]. Moreover, characterization of essential oils fraction of Salvia sclarea flower identified β–myrcene, linalool, α–terpineol, cinnamaldehyde, linalyl acetate and geranyl acetate as the major component which was responsible for the 52% higher H1N1-CPE inhibition compared to the standard drug, oseltamivir [ 108 ].…”
Section: Application Of Salvia Species In Cancer P...mentioning
confidence: 96%
“… Salvia species Virus Cell culture, Study model Assay Duration of treatment/Incubation time Activities (IC 50 /EC 50 ) References Salvia cyanescens Boiss. & Balansa HSV-1 PI- 3 MDBK and Vero cell lines cytopathogenic effect (CPE) concentrations 48 h 16–1.0 mg/ml against both HSV-1 and PI-3 [ 101 ] Salvia dentata H1N1 MDCK cells plaque reduction assay (PRA) 108 h 93% [ 16 ] Salvia microstegia Boiss. & Balansa HSV-1 PI- 3 MDBK and Vero cell lines cytopathogenic effect (CPE) concentrations 48 h 16–1.0 mg/ml against both HSV-1 and PI-3 [ 101 ] Salvia cedronella Boiss H7N7, H3N2,HSV-1 & HSV-2 MDCK and MDBK cells Cytopathogenic effect (CPE) reduction assay 24 h 0.30 mg/ml (H7N7), 0.60 mg/ml (H3N2), 0.60 mg/ml (HSV-1) & 0.50 mg/ml (HSV-2) [ 107 ] Salvia desoleana Atzei Acyclovir sensitive (AS) and Acyclovir resistant (AR) strains HSV-2 Vero, (ATCC CCL-81), the epithelial cell lines Hep-2 (ATCC CCL-23) and A549 (ATCC CCL-185) HSV inhibition assay Tim of Addition Assay Virus inactivation assay 2 h 23.72 μg/ml (AS) 28.57 μg/ml (AR) [ 104 ] Salvia fructicosa Mill.…”
Section: Application Of Salvia Species In Cancer P...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 38 ], S. officinalis [ 39 ], S. dentata Aiton, S. scabra Thunb. [ 40 ]); and antimicrobial ( S. euphratica Montbret, S. kornenburgii Rech. f. [ 41 ], and S. chamaedryoides [ 42 ]).…”
Section: Introductionmentioning
confidence: 99%